Islamic Law’s role in developing policies prohibiting homosexuality as a crime against morality in Indonesia - Widyawati, Anis; Arifin, Ridwan; Setyanto, Heru; Syahputra, Bearlly Deo; Sabri, Zaharuddin Sani Ahmah (Faculty of Law, University of Muhammadiyah Malang, 2024)
This research examines the significance of the Islamic law doctrine's role in the development of policies aiming to prohibit homosexuality as a crime against morality in Indonesia. The study focuses on the foundational contributions and core principles of Islamic law that form the basis for shaping policies concerning the issue of homosexuality. The research methodology involves an in-depth analysis of primary Islamic legal sources and an exploration of Indonesia's positive legal framework that influences the direction of these policies. Furthermore, the research encompasses legal case studies, an exploration of relevant literature, and an Islamic legal perspective regarding the efforts to prohibit homosexuality. Consequently, the research results deepen the understanding of the contributions and relevance of Islamic law in formulating policies that regulate homosexuality as a crime against morality in Indonesia. Moreover, this study aims to identify challenges and opportunities associated with implementing these policies.